2017
DOI: 10.1016/j.jeoa.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Too old to work, too young to retire?

Abstract: We study whether employment prospects of old and young workers differ after a plant closure. Using Austrian administrative data, we show that old and young workers face similar displacement costs in terms of employment in the long-run, but old workers lose considerably more initially and gain later. We interpret these findings using a search model with retirement as an absorbing state, that we calibrate to match the observed patterns. Our finding is that the dynamics of relative employment losses of old versus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 25 publications
3
32
0
1
Order By: Relevance
“…Economists have shown that the loss of a job due to a plant closure can have major disruptive effects on future careers of workers (Jacobson et al (1993), Fallick (1996) or Ichino et al (2016)). They studied only plant closure effects for average persons, whereas our analysis applies model-based clustering to explicitly address unobserved heterogeneity in reaction to loosing a job due to an exogenous event such as a plant closure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Economists have shown that the loss of a job due to a plant closure can have major disruptive effects on future careers of workers (Jacobson et al (1993), Fallick (1996) or Ichino et al (2016)). They studied only plant closure effects for average persons, whereas our analysis applies model-based clustering to explicitly address unobserved heterogeneity in reaction to loosing a job due to an exogenous event such as a plant closure.…”
Section: Discussionmentioning
confidence: 99%
“…However, the assumption that the long-run career paths of workers who experienced plant closure follow a time-homogeneous Markov chain is not realistic (see Ichino et al (2016) , Figure 2). A descriptive investigation of the evolution of the employment rate over distance to plant closure reveals that the employment rate does not converge to a steady state, but rather declines steadily with increasing distance to plant closure.…”
Section: Time-varying Mixture-of-experts Markov Chain Clusteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Ichino et al. () show that although displaced workers in the age group 45–55 face reduced re‐employment probabilities compared with prime‐age workers, their employment prospects catch up over a period of two consecutive years. However, displacement of older workers is hindered by employment protection legislation such as the layoff tax, which has been shown to reduce displacement probabilities for older workers .…”
Section: Microsimulationsmentioning
confidence: 99%
“…A study developed by Burtless and Quinn (2002) [8] with America as the research object indicated raising the age of retirement, especially that of women, in America after 1980s did bring some benefits to both individuals and national economy and promote the economic development. Ichino (2007) [9] expounded the substitution relation between senile workers and young ones to prove that the pension payment pressure could be alleviated through postponed retirement on the prerequisite that the employment prospect of senile workers was never deteriorating. The research conducted by Bloom, Canning and Fink (2010) [10] suggested aging population-induced economic recession could be resisted if the government postponed the retirement.…”
mentioning
confidence: 99%